2020
DOI: 10.1111/aos.14526
|View full text |Cite
|
Sign up to set email alerts
|

The effect of successful trabeculectomy on the ocular surface and tear proteomics—a prospective cohort study with 1‐year follow‐up

Abstract: Purpose To report changes in the ocular surface and tear proteomics after discontinuation of chronic glaucoma medication. Methods Patients requiring trabeculectomy were recruited from the glaucoma clinic of Tampere University Hospital, Finland. Fifty‐seven patients with previous history of anti‐glaucomatous eye drops (8.1 ± 6.8 years) and having undergone a successful trabeculectomy were included in this report. Outcomes of interest were conjunctival redness grading, tear secretion (Schirmer I) and tear film p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…We assumed conjunctival hyperemia as a primary outcome. Hyperemia is present in nearly all medically treated eyes ( p 1 = 0.95), and surgery is frequently associated with hyperemia reduction; we assumed a 40% reduction of hyperemia as clinically relevant ( p 2 = 0.55) [ 27 , 28 , 29 ]. With α/2 = 0.05 and β = 0.8, Δ = 0.40, 25 patients were necessary in this study.…”
Section: Methodsmentioning
confidence: 99%
“…We assumed conjunctival hyperemia as a primary outcome. Hyperemia is present in nearly all medically treated eyes ( p 1 = 0.95), and surgery is frequently associated with hyperemia reduction; we assumed a 40% reduction of hyperemia as clinically relevant ( p 2 = 0.55) [ 27 , 28 , 29 ]. With α/2 = 0.05 and β = 0.8, Δ = 0.40, 25 patients were necessary in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Burgos-Blasco et al [ 105 ] identified that high levels of IL8 in tears could predict lower IOP reduction. A study by Vaajanen et al [ 106 ], on the other hand, examined how the tear protein levels change after trabeculectomy. In this study, trabeculectomy patients were followed for 1 year after surgery and the results indicated an improvement in the ocular surface state both clinically and at the protein level.…”
Section: Tear Fluid Proteomics In the Evaluation Of Therapeutic Outco...mentioning
confidence: 99%
“…Although OSD caused by glaucoma filtration surgery is common, given that the long-term use of anti-glaucomatous medications and topical steroid infusion after surgery may have a positive impact on the ocular surface status, surgical treatment is still beneficial to reduce OSD [159,160]. A 1-year follow-up study showed the improved conjunctival state, the decreased level of pro-inflammatory protein, and the enhanced function related to lipid transport in patients after trabeculectomy [161]. In addition, selective laser trabeculoplasty or minimally invasive glaucoma surgery may be a more appropriate choice for patients with glaucoma and OSD.…”
Section: Surgical Treatmentmentioning
confidence: 99%